Serbia: Public Finance – Toward the Efficient Management of the Country’s Revenues - Popović, Dušan V. (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
Like other countries of South-East Europe, the Republic of Serbia aims to join the European Union (EU). Within the Stabilisation and Association Process, Serbia has undertaken steps to harmonise its national legal system with that of the EU, as well as actions that seek to establish a functional market economy. However, Serbia’s present geopolitical position outside of the EU allows for a larger autonomy in conducting its national economic policy. This chapter examines the particularities of the elaboration and enforcement of fiscal policy, and more specifically public finance, from the perspective of an EU candidate country. The Serbian public finance system is not fully aligned with EU law; however, the reforms implemented thus far were considered sufficient for opening the EU-Serbia negotiation chapters (now, clusters) pertaining to the area of public finance. Under the general fiscal rules prescribed by the Budget System Act, the government sector debt, including the liabilities based on restitution, should not exceed 60% of gross domestic product (GDP), while the target medium-term fiscal deficit should represent 0.5% of the GDP. Under the principles of responsible fiscal management, the employee expenses in the government sector must be fixed at a sustainable level; thus, efforts are made to keep the proportion of these expenses in the GDP under 10%. Although the budgetary procedure is well designed, the ‘regular’ path for budget adoption was not always observed in the past, mainly due to economic perturbations caused by the COVID-19 pandemic.Keywords: public finance, Serbia, budget, European integrations, Fiscal Council